A syndrome of insulin resistance resembling leprechaunism in five sibs of consanguineous parents. Issue 6 (June 1993) - al-Gazali, L I; Khalil, M; Devadas, K
Abstract : Leprechaunism is a rare autosomal recessive disorder associated with extreme insulin resistance with paradoxical hypo-glycaemia. It is characterised by prenatal and postnatal growth retardation, reduced subcutaneous tissue, coarse features, acanthosis nigricans, enlarged genitalia, and death in the first year of life. Defects in both the insulin receptor and postreceptor steps of the insulin action pathway have been reported. At the molecular level, several mutations have been described. The patients reported here are from a Yemeni family with a syndrome of insulin resistance similar to leprechaunism in which the parents are second cousins and five of their eight children are affected. However, the phenotypes seem to be less severe than the classical leprechaunism previously described. All the children are alive (oldest 11 years), there is normal subcutaneous tissue, and a normal growth pattern in some of them. It may be that this is a milder type of leprechaunism with a better prognosis, perhaps caused by a different type of mutation from those previously described.